Pediatric pulmonology, asthma, and sleep medicine : a quick reference guide (American Academy of Pediatrics, 2018)
"Obtain practice-focused guidance on the diagnosis, evaluation, and treatment of the most commonly encountered pediatric respiratory conditions, asthma-related difficulties, and sleep disorders. Starting with the signs, symptoms, and conditions most commonly encountered in primary pulmonary care, the book provides advice for appropriate testing, treatment plans, and common complications for which to watch. Topics include: Evaluation of Children With Respiratory Disease Anatomic Disorders and Congenital Anomalies of the Airway, Lungs, Pulmonary Vessels, and Chest Wall Asthma and Related Conditions Infections of the Respiratory Tract Genetic Respiratory Diseases Pediatric Sleep Medicine Pediatric Respiratory Care Miscellaneous Respiratory Diseases Respiratory Disease in Association With Other Systemic Diseases Special expanded sections on asthma, sleep medicine, and respiratory care provide non-specialists with the knowledge needed to effectively treat these often-complicated conditions. Each chapter is presented in a concise, bulleted format with tables and figures that make it easy to locate key information. Also included is direction on when to refer patients who require the care of a pulmonary specialist"--Publisher's description